2006
DOI: 10.1002/qua.21269
|View full text |Cite
|
Sign up to set email alerts
|

Features of the potential energy surface for the reaction of HO2 radical with acetone

Abstract: ABSTRACT:The mechanism of the reaction of acetone with HO 2 has been studied by quantum chemical computations. Different stationary points on the potential energy surface (PES) of the reaction have been characterized. These stationary points are the reactants, products, molecular complexes, and transition states. Three pathways have been studied: two H-abstraction channels and one HO 2 -addition channel. The MP2 level of theory with the 6-311G(d,p) basis set was employed for geometry optimization. The electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“… have directly detected the peroxy radical HOCH 2 O 2 by IR and near IR spectroscopy and have found that the appearance rate from the reaction is consistent with direct formation by reaction (R1b). The experimental results are consistent with calculations, which indicate that the barrier for reaction (R1b) is high in the case of acetone , but much lower than the energy of the initial reactants, HO 2 + CH 2 O, in the case of formaldehyde . Therefore, we have evaluated our experimental data by considering a single equilibrium reaction.…”
Section: Resultssupporting
confidence: 85%
“… have directly detected the peroxy radical HOCH 2 O 2 by IR and near IR spectroscopy and have found that the appearance rate from the reaction is consistent with direct formation by reaction (R1b). The experimental results are consistent with calculations, which indicate that the barrier for reaction (R1b) is high in the case of acetone , but much lower than the energy of the initial reactants, HO 2 + CH 2 O, in the case of formaldehyde . Therefore, we have evaluated our experimental data by considering a single equilibrium reaction.…”
Section: Resultssupporting
confidence: 85%
“…Also displayed on Fig. 4 are lines representing K 1 (T ) values from Hermans et al (2004) and Cours et al (2007), neither of which are well-reproduced by the results from this work. Striking however, is the coincidence of the equilibrium constants derived in this work, with the predictions for K 1a from Aloisio and Francisco (2004), and the recent experimental determinations from Grieman et al (2011).…”
Section: Simulations Varying K 1 (T ) K 1 (T ) and K 2 (T )supporting
confidence: 68%
“…2). This simulation (indistinguishable from simulations using values of k 1 and K 1 from Cours et al, 2007) clearly underestimates the impact of [CH 3 C(O)CH 3 ] = 1 × 10 15 molecule cm −3 on the observed OH profile (the blue circles), suggesting a good experimental sensitivity, and that CH 3 C(O)CH 3 does indeed interact strongly with HO 2 at this temperature. Note that the small differences in the simulations with [CH 3 C(O)CH 3 ] = 0 (black solid line), and the k 1 = 0 green, dotted line were principally due to an increased OH removal rate via reaction with the added acetone (R4), and to a lesser extent scavenging of the Cl precursor (R11).…”
Section: Numerical Simulations Of the (R1) Datamentioning
confidence: 64%
See 1 more Smart Citation
“…The oceans act as either sources or sinks, depending on light, microbial activity, and water temperatures [ Wisthaler et al , 2002; de Laat et al , 2001; Warneke and de Gouw , 2001; Singh et al , 2003]. Besides dry deposition to ocean and land surfaces, major sinks are the reaction with OH, photodissociation in the UV [ Folkins et al , 1998; Wennberg et al , 1998], and reaction with HO 2 at low temperatures in the upper troposphere/lowermost stratosphere (UT/LMS) [ Hermans et al , 2004, 2005; Cours et al , 2007].…”
Section: Introductionmentioning
confidence: 99%